THE CORRELATION BETWEEN FAMILY FUNCTIONING AND QUALITY OF LIFE OF CAREGIVER OF CHILDREN WITH LEUKEMIA - Annisha Fadhilla; Ikeu Nurhidayah; Fanny Adistie (Belitung Nursing Journal, 2019)
Background: Quality of life of caregiver of children with leukemia is important because it can affect the quality of care provided and can affect the health of children and the caregiver themselves. One of the factors that influence the caregiver’s quality of life is the family functioning. However, a few number of research on the correlation of family functioning in the caregiver's situation. Objective: The aim of the study was to analyze the correlation between family functioning and the caregiver’s quality of life of children with leukemia. Methods: This study used a Quality of Life Family Version questionnaire and a Family Assessment Device questionnaire. The populations in this study were all parents (father or mother) who were the primary caregiver of children with leukemia aged 0-15 years and were being treated at a referral hospital in West Java, Indonesia. Thirty-two respondents were determined by a total sampling technique. The data analysis used frequency distribution and chi-square. Results: The results showed that the family functioning and quality of life of the caregiver had the same results, 50% good and 50% poor. Correlation test in this study showed a negative value with p value > 0.05 (0.480), which indicated that there was no correlation between family functioning and the quality of life of the caregiver. Conclusion: The correlation between family functioning and caregiver's quality of life was not significant. This is likely due to the variable family functioning and the caregiver’s quality of life having balanced results. The results of this study need to be followed up by providing nursing care holistically not only to children, but also to families, especially who are directly involved in child care.